The Burning Spear: Being the Experiences of Mr. John Lavender in the Time of War - Galsworthy, John, 1867-1933 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Burning Spear" by John Galsworthy is a satirical novel that appears to examine the experiences of Mr. John Lavender during the tumultuous time of war, likely set in the World War I era. The story centers around Lavender, a somewhat eccentric and idealistic gentleman who craves a sense of purpose and dedication to his country amidst the chaos of war, grappling with his own nerves and perceptions of patriotism. The opening of the novel introduces Mr. Lavender as a gentle and somewhat whimsical character living an isolated life on Hampstead Heath, accompanied by his sheepdog, Blink. Disturbed by the war, he becomes increasingly consumed with a desire to contribute positively to the national effort, which leads him to seek out a role as a public speaker. His initial attempts are met with various humorous obstacles, including comical interactions with his housekeeper and chauffeur, as well as a series of misadventures that reflect the absurdity of wartime patriotism. As Lavender embarks on his new role, the reader gains insight into his quirky ideals and the social landscape of the time, all steeped in Galsworthy$1 (Bs trademark wit and critical commentary. (This is an automatically generated summary.)s
Release date is 2006-06-14
Produced by David Widger
Keywords: World War, 1914-1918 -- Humor, caricatures, etc